Considerations for a computer model for the hepatic circulation under chronic Budd-Chiari syndrome conditions. (September 2019) - Ho, H.; Qiu, C.
Abstract: In this response to the Letter to Editor we discuss the methods for transforming our recently published computer model for the Budd-Chiari syndrome (BCS) into a model which is more suitable for accounting for the aetiology difference in the West and the East. In particular, the electronic components in the computer model need to be time-dependent, while incorporating the time occurrences of the clinical observations of hepatic arterial and portal flows under chronic BCS conditions.